Mosques as the heart of Islamic social finance: innovative roles and significances - Mohd. Zain, Nor Razinah; Shah, Hassan Shakeel (2019)
Mosques continue to be built across the globe. While, certain countries are still adapting to existence of mosques within their societies, majority countries of Middle East are religiously and culturally engraved with the functions of mosques. While the world is witnessing the steady growth of Islamic financial services, it opens a new paradigm of study in appreciating the implementation of Islamic social finance. The so-called traditional Islamic philanthropies instruments as introduced by the divine revelation i.e. Qur’an and the practices of Prophet Muhammad (bless and peace be upon him) remain relevant to the sustainability and development of the societies. Moreover, it is found that mosques have functions to increase such implementation of Islamic social finance. Innovatively, the disruption of technology in this millennium indicates certain innovative functions of mosques toward improving the lives of the people that stay close to them.